Mental Models Based on Students Thinking Style About Objects in Static Fluid - Gustina; Jusman Mansyur; Wahyuni N Laratu; Rahmat Tule (Postgraduate, University of Mataram, 2024)
This study aims to describe a mental models based on students' thinking styles about objects in static fluids. The type of research used is quasi-qualitative with a research design using Simple Research Design (SRD). This research was carried out at MAN Insan Cendikia, Palu City for grade XII students in the 2023 academic year, with 30 students as subjects. The instruments of this research are questionnaires, two-level test and interview guide. The data analysis technique used is the